Programa de valorização pelo mérito implantado pela secretaria do estado da educação de São Paulo: opiniões de professores coordenadores - Marques, Lígia Maria (2012)
This research discusses the Valorization Program by Merit implemented by the State Education Board of São Paulo in 2009. The purpose is to analyze, in the context of educational policies implemented in the Education System of São Paulo, possible consequences of its introduction in the teaching career and in the dynamics of the school work, by the point of view of coordinating teachers. It explores how the notion of meritocracy in the current education policies has been materializing. In order to do so, it explains the purposes and delineation of the Program, relating them to the directives of the educational public policies of the Estate of Sao Paulo, and it analyses the opinions of coordinating teachers about the Merit Program and its possible effects in the school work dynamics. This exploratory research has utilized procedures based upon a qualitative approach, resorting to the analysis of document sources and testimonials gathered by a semi-structured questionnaire, with open and closed questions. National and International authors that have studied the evaluation theme and the teaching career subsidized the results discussion. The results demonstrate the tendency to accept the notion of fairness of the Valorization Program by Merit. The discrepancy with the Program usually refers to the adopted criteria, which reveals the acceptance of the idea of teachers’ accountability by their choices, trajectories and by the results reached in their lives, which make us believe that success and failure are attached to the talent and abilities of each individual. The Program, while adopting the meritocracy principle, has potential to induce discriminatory practices where only “the best” and “the most capable” must be awarded by their individual efforts. As outlined, awarding only 20% of teachers induces the division of the “the most well prepared” group and “the not well prepared” group, in addition to promoting competition and encouraging the enhancement of individualized education. Therefore, it trails in the opposite direction of a collaborative culture, which encourages values such as sharing between members of the school.